2006
DOI: 10.1007/s00232-006-0035-0
|View full text |Cite
|
Sign up to set email alerts
|

The Third Sodium Binding Site of Na,K-ATPase Is Functionally Linked to Acidic pH-Activated Inward Current

Abstract: Sodium- and potassium-activated adenosine triphosphatases (Na,K-ATPase) is the ubiquitous active transport system that maintains the Na(+) and K(+) gradients across the plasma membrane by exchanging three intracellular Na(+) ions against two extracellular K(+) ions. In addition to the two cation binding sites homologous to the calcium site of sarcoplasmic and endoplasmic reticulum calcium ATPase and which are alternatively occupied by Na(+) and K(+) ions, a third Na(+)-specific site is located close to transme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
28
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 31 publications
5
28
0
Order By: Relevance
“…S2). It has been proposed that an increase in [H o ϩ ] makes the internal gate permissive to H ϩ and Na ϩ (at low Na o ϩ ) flow through the exclusive Na ϩ site (21). Thus, one interpretation of our results may be that the C-terminal deletion alters the intracellular gate and thus destabilizes ion occlusion.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…S2). It has been proposed that an increase in [H o ϩ ] makes the internal gate permissive to H ϩ and Na ϩ (at low Na o ϩ ) flow through the exclusive Na ϩ site (21). Thus, one interpretation of our results may be that the C-terminal deletion alters the intracellular gate and thus destabilizes ion occlusion.…”
Section: Discussionmentioning
confidence: 61%
“…S2). This H ϩ current has been described in endogenous (12), wild-type (19), and mutant Na/K pumps (20,21) expressed in Xenopus oocytes and has been proposed to represent downhill transport of H ϩ through the exclusive Na ϩ binding site when the pump is in E2P (21,22). As the two currents present similar voltage dependencies, TEVC was used to study the [Na o ϩ ] dependence of ouabain-sensitive steady-state current in the absence of K o ϩ in RD⌬KESYY pumps.…”
Section: Effects On Na Omentioning
confidence: 56%
“…S5), probably resulting from electrogenic uncoupled Na + efflux (a conclusive determination of its nature exceeds the scope of this report), and an uncoupled inward current observed during negative voltage pulses, which has been associated with an ion pathway through site III. The (19,20) is thought to represent electrochemically dissipative H + flow through site III of the Na,K-ATPase (9,12,13). This transport mode appears too slow and rate limited by protein conformational changes to represent simple ion flow through an ion channel (12,21).…”
Section: Resultsmentioning
confidence: 99%
“…S2). In addition, several studies have proposed a noncanonical mode of transport in which protons move in the inward direction down their electrochemical gradient at very negative voltages (11) through a pathway that passes through site III (9,10,12,13).…”
mentioning
confidence: 99%
“…Poulsen et al (5) have previously suggested that a cavity between TM5, TM7 and TM8 provides cytoplasmic access in the E2P conformation for protonation of D926 and proton leak currents (30,31). Cytoplasmic access to this cavity was also postulated to be blocked in the E1P conformation by the C-terminal hydrogenbond network (5).…”
Section: Molecular Mechanism Of Selectivity In Namentioning
confidence: 99%